Pension Management System of PRBS in the Philippine National Police: Ba-sis for Policy Enhancement - Layugan, Alan A.; Tanigue, Yolanda; Villa, Elizabeth B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study assessed the pension management system of the PRBS in the Philippine National Police, highlighting specific challenges and deficiencies in different areas. These challenges include ensuring the completeness and legality of supporting documents, addressing delays in the issuance of updated documents from the Philippine Statistics Authority (PSA), improving the process of updating and issuing records, and enhancing the feedback mechanism and incorporation of results in the PRBS Program Review and Analysis. There are variations in beneficiaries' perceptions across different aspects of the pension management system, indicating room for improvement. Recommendations include establishing clear guidelines, enhancing communication channels, streamlining processes, and prioritizing solutions favored by beneficiaries. The study also recommends implementing clear guidelines, standardized checklists, training programs, and streamlined processes to address the challenges. These measures, if adopted, could significantly improve the efficiency and effectiveness of the pension management system. Enhancing communication and coordination with the PSA, implementing technological solutions, and establishing a feedback mechanism are also advised. Further, analysis is suggested to understand specific problems and differences in perception. Recommendations also focus on improving access to claim status information, prioritizing beneficiary-favored solutions, and enhancing policy implementation of the Pension Management System. These changes, if implemented, could lead to a more transparent, efficient, and beneficiary-friendly pension management system. Your active participation in this process is crucial and highly valued. In summary, the study highlights the challenges, recommendations, and conclusions related to the pension management system in the Philippine National Police, emphasizing the need for improvements in various aspects to enhance efficiency, effectiveness, and satisfaction among pensioners and stakeholders.